Négocier ses besoins dans un univers contraint. Le renoncement aux soins en situation de précarité - Caroline Desprès (Anthropologie & Santé)
This article examines the multiple causes which explain healthcare renunciation in the context of economic deprivation. It aims at understanding how individuals determine their individual and familial therapeutic behaviors when they are subjected to strong socioeconomic constraints. This research is based on an empirical study conducted in metropolitan Lille (France) but essentially focuses on a case study. This example highlights the articulations between different ways of thinking so as to underline the thought processes and the necessary compromises one has to make between different norms and personal standards, while taking into account the temporal dimension of past and present experiences.